Analisis K3 Pada Pekerja Bagian Proses Fabrikasi Plate Tangki dengan Metode Hirarc di PT. XYZ - Khotibul Umam; Suseno Suseno (Pusat Riset dan Inovasi Nasional, 2025)
Abstract. Occupational Health and Safety (OHS) is a critical component of the workforce system to protect workers from workplace accidents and occupational diseases. PT XYZ faces high risks due to field activities, making the implementation of an OHS management system based on HIRARC (Hazard Identification, Risk Assessment, and Risk Control) an effective solution to prevent accidents. The plate tank fabrication process identifies 23 potential hazards from five activities, including crane lifting, welding, and grinding, which pose risks such as fires, injuries, and health issues. Risk analysis results reveal high to moderate risks. After mitigation, the risks were reduced to low to moderate categories. Mitigation efforts include worker training, regular inspections of work equipment, and improving ventilation in work areas. Risk control measures are systematically applied following the OHSAS 18001 hierarchy, including hazard elimination, substitution, engineering controls, administrative controls, and the use of personal protective equipment (PPE). The implementation of